Evaluación de la adaptación de cinco cultivares de coliflor (Brassica oleracea var. Botrytis) en el barrio Anchilivi, Salcedo, Cotopaxi. - Martínez Toaquiza, Joselyn Fernanda (2024)
This research was carried out in the Anchilivi neighborhood, Canton Salcedo, Cotopaxi Province, to evaluate the adaptation of five cultivars of cauliflower (Brassica oleracea var. Botritys). The cultivars were provided by the company "Semillas Capelo", those were AX3098, EM944, EM977, Skywalker and Bodilis which is the control, four replications were established, resulting in 20 experimental units, each experimental unit measured 10 m², with a total area of 299 m², a DBCA was used with the variables under study and the Tukey test at 5% with the factors that presented organic significance. The methodology used was quantitative, the results were recorded quantitatively (equatorial diameter, height, weight, rejection % yield, days to harvest) and qualitatively (shape, color, compactness, envelope, uniformity and tolerance to pests and diseases). The cultivar with the best result was AX3098 in the variable height at 60 days (36.5 cm) and tolerance to pests and diseases evaluated on a scale of 4 equal to (symptoms) and the cultivar EM944 has the best results in terms of the variables diameter of the pellet (17.5 cm), weight of the pellet (486.25g), rejection (136. 25 g), pellet compactness on a scale of 5 (slightly compact), with the highest yield (3161 kg/ha) and required 76 days to harvest. Cultivar EM944 was best adapted the Anchilivi neighborhood, Canton Salcedo, Cotopaxi Province.